2021
DOI: 10.1029/2020sw002676
|View full text |Cite
|
Sign up to set email alerts
|

Daytime Equatorial Spread F‐Like Irregularities Detected by HF Doppler Receiver and Digisonde

Abstract: The ionosphere is an indispensable medium for the propagation of communication and navigation signals. It has been extensively studied over the years to understand its properties and variability under different conditions. Spread F (SF) is a common feature of the ionosphere that is caused by irregularities in electron density distribution in the F-layer. Radio signals incident on these irregular plasma structures are scattered, thereby causing diffuse spreading in the F-layer trace of ionograms. Bottomside spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Olugbon et al. (2021) also pointed out that changes in ionospheric ED appeared about the same time that large amplitude oscillations appeared in F‐layer plasma. Changes in ionospheric conductivity have been previously reported to cause a change in the polarization of ultra‐low frequency waves at low and equatorial latitudes (Saka et al., 1980, 1982, 1988).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Olugbon et al. (2021) also pointed out that changes in ionospheric ED appeared about the same time that large amplitude oscillations appeared in F‐layer plasma. Changes in ionospheric conductivity have been previously reported to cause a change in the polarization of ultra‐low frequency waves at low and equatorial latitudes (Saka et al., 1980, 1982, 1988).…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, for the first event reported, harmonic frequencies were observed in the spectra of ΔsTEC from LGLA when compared with those from ABFC. Olugbon et al (2021) also pointed out that changes in ionospheric ED appeared about the same time that large amplitude oscillations appeared in F-layer plasma. Changes in ionospheric conductivity have been previously reported to cause a change in the polarization of ultra-low frequency waves at low and equatorial latitudes (Saka et al, 1980(Saka et al, , 1982(Saka et al, , 1988.…”
Section: Eventmentioning
confidence: 90%
See 1 more Smart Citation
“…It is worthy to note that Olugbon et al. (2021) presented two daytime equatorial spread F events by the HF Doppler receiver and indicated that wave structures related to TIDs were responsible for the daytime ESF‐like irregularities. In the middle latitude regions, Bowman et al.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al (2020) reported the post-sunrise plasma irregularities at low latitude region during a moderate geomagnetic storm and considered that these plasma irregularities were not developed from the previous night, but were newly generated near sunrise hours due to the disturbance of the dynamo electric field. It is worthy to note that Olugbon et al (2021) presented two daytime equatorial spread F events by the HF Doppler receiver and indicated that wave structures related to TIDs were responsible for the daytime ESF-like irregularities. In the middle latitude regions, Bowman et al (1987) found that distorted traces of the main traces on daytime ionograms were caused by the passage of TIDs, and suggested these daytime distorted traces was a kind of the spread F-phenomenon.…”
mentioning
confidence: 97%